Case Research of Personology of Filipino Children in Conflict with the Law (CICL) - Jemerson Naceno Dominguez (PSIKODIMENSIA, 2020)
In the Philippines, afar from the usual attachment, a child sometimes leads to offend out of survival necessity that leads to total separation from their family, this explains a phenomenon of conflict to the law. Aiming to describe the profile and personology of CICL in Bahay Kalinga; and its correlates. Case research was used in analyzing violations, family structure and personology among 20 participants. In-house CICL’s profile depicted: 15 years and 9 months as average age; substantial number of boys committed offences than girls; commonly falls below poverty rate; majority stop schooling; all own a dysfunctional family; and affirmed 4-5 family members. Regarding personology, mostly verified an average self-concept, majority pointed out having realistic self-image, and beyond median represented low self-esteem. Descriptions and measures of their profile and personology could determine the risk of being CICL. The patterns of personology were focused through the information of their extracted statements. Personology traits and types play a vital role in the concepts described by Filipino CICL. Thus, there were seven themes that build up the collection of personology as precedents of traits and patterns. Replicate the study to establish Philippine norm of cases associated with conflict of the law.